Cancer patient’s experiences with the use of mHealth during the chemotherapy treatment: a qualitative systematic review protocol - Magalhães, Bruno (2023)
Introduction: Identifying the perception or experiences associated with the use of mobile applications (mHealth) during chemotherapy treatment is essential to ensure patient involvement. This indentification is also fundamental in the development process of this type of solutions.  Therefor the present study intended to synthesize the knowledge produced about the perceptions or experiences of people with oncological disease resulting from the use of mobile applications, used during chemotherapy treatment. Inclusion Criteria: The review will consider all primary studies with a qualitative methodological approach, published in English, French, Spanish or Portuguese, until December 31, 2022. Methods: The review will be conducted according to the JBI methodology for systematic reviews of qualitative evidence. Electronic databases MEDLINE®, CINAHL®, Psychology and Behavioral Sciences Collection, Scopus® and Cochrane Library will be used to identify primary studies. Data extraction will be performed using a tool developed by the researchers, based on the JBI model (JBI QARI Data Extraction Tool for Qualitative Research). Extracted data will, where possible, be grouped using a meta-aggregation approach. The summary of the findings will be presented using ConQual in order to assess the confidence in the findings. Systematic review registration umber: PROSPERO (CRD42020213811)